2018
DOI: 10.1177/0363546518770415
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Proud Large Osteochondral Plugs on Contact Forces and Knee Kinematics: A Robotic Study

Abstract: Increased CF and altered knee kinematics from a proud femoral plug could affect graft viability. Plug proudness of only 0.5 mm produced significant changes in CF and knee kinematics, and the clinically accepted 1-mm tolerance may need to be reexamined in view of our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…They found significant increases in contact pressure with both sunken ( P < .01) and proud ( P < .01) grafts compared with intact cartilage at both 0.5 and 1 mm. In another study, Du et al 8 investigated how a large (>20 mm) proud graft influences tibiofemoral contact forces in a cadaveric model. They found that increasing the proudness of a medial OCA in 20° of flexion by 0.5, 1, and 1.5 mm resulted in an increase in contact pressures of 80 N (36%), 155 N (70%), and 193 N (87%), respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found significant increases in contact pressure with both sunken ( P < .01) and proud ( P < .01) grafts compared with intact cartilage at both 0.5 and 1 mm. In another study, Du et al 8 investigated how a large (>20 mm) proud graft influences tibiofemoral contact forces in a cadaveric model. They found that increasing the proudness of a medial OCA in 20° of flexion by 0.5, 1, and 1.5 mm resulted in an increase in contact pressures of 80 N (36%), 155 N (70%), and 193 N (87%), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The Fisher exact test was utilized to compare the number of minimal clinically adequate allografts (with thresholds of 0.5 and 1 mm) between the overlapping and oblong groups. 8,9,22 Finally, the F test was performed to analyze differences in variance between groups. Significance was set at P < .05.…”
Section: Methodsmentioning
confidence: 99%
“…The deleterious effects of an incongruous OCA graft, either proud or recessed, are well documented in several biomechanics studies, including a recent cadaveric study from our biomechanics laboratory that revealed graft contact forces for proud medial femoral condyle (MFC) grafts were increased 36% (0.5 mm) and 70% (1 mm) and contact forces for proud lateral femoral condyle (LFC) grafts increased 14% (0.5 mm) and 29% (1 mm). [4][5][6] However, as my referral practice for cartilage restoration procedures matured, I found both myself and my patients were not entirely happy with the protracted wait times and the need to add cases on unexpectedly at the last minute to take advantage of a potential graft before it expired. Ultimately, I decided to become adept at using nonorthotopic OCA grafts because I knew I had to somehow make the supply meet the demand.…”
Section: See Related Article On Page 3033mentioning
confidence: 99%
“…The threshold of 0.5 mm of incongruity resulting in significantly increased contact pressures has been supported in other cadaveric studies. 3,4 These studies demonstrate the importance of ensuring that the osteochondral allograft is flush with the surrounding articular surface; one of the main issues that leads to graft incongruity is differences between donor and recipient radius of curvature.…”
mentioning
confidence: 99%